Studies of the benzopyran class of selective COX-2 inhibitors using 3D-QSAR and molecular docking - Yadav, D.; Saloni; Sharma, P.; Misra, S.; Singh, H.; Mancera, Ricardo; Kim, K.; Jang, C.; Kim, M.; Pérez-Sánchez, H.; Choi, E.; Kumar, S. (Pharmaceutical Society of Korea, 2017)
Abstract: The Gaussian-based 3D-QSAR studies for 58 selective COX-2 (cyclooxygenase-2) inhibitors belonging to benzopyran chemical class were performed. Partial least squares analysis produced statistically significant model with (R training 2 = 0.866) and predictability (Q training 2 = 0.66, Q test 2 = 0.846). The 3D-QSAR model includes steric, electrostatic, hydrophobic, and hydrogen bond acceptor field indicators, whereas the potential field contributions indicate that the steric and hydrophobic features of the molecules play an important role in governing their biological activity. A molecular docking simulation and protein–ligand interaction pattern analysis reveal the importance of Tyr-361 and Ser-516 of the COX-2 active site for X- ray crystal structures and this class of molecules. Thus the combined approach of ligand-based and structure-based models provided an improved understanding in the interaction between benzopyran chemical class and COX-2 inhibition, which will guide the future identification of more potent anti-inflammatory drugs.